If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 = 2(3k + 1) + -4 Reorder the terms: 18 = 2(1 + 3k) + -4 18 = (1 * 2 + 3k * 2) + -4 18 = (2 + 6k) + -4 Reorder the terms: 18 = 2 + -4 + 6k Combine like terms: 2 + -4 = -2 18 = -2 + 6k Solving 18 = -2 + 6k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-6k' to each side of the equation. 18 + -6k = -2 + 6k + -6k Combine like terms: 6k + -6k = 0 18 + -6k = -2 + 0 18 + -6k = -2 Add '-18' to each side of the equation. 18 + -18 + -6k = -2 + -18 Combine like terms: 18 + -18 = 0 0 + -6k = -2 + -18 -6k = -2 + -18 Combine like terms: -2 + -18 = -20 -6k = -20 Divide each side by '-6'. k = 3.333333333 Simplifying k = 3.333333333
| 4x+48=12x | | x^2+10=154 | | 2.5x+6=60 | | 2y^2+3y-35= | | 8y=33-5y | | 9d-9=18 | | 9u=4u+35 | | 6m+4m-m+5=23 | | 6(x+3)-20=32 | | 3x-5x+1=8-2x | | 2x+3+0.75= | | 9y^2+18y+8= | | x^2-16x-132=0 | | 10=30(20)+b | | y=ln(x+2)-4 | | 10(x-2)+12(x+4)=x | | 9x-37=12x+23 | | -7y-2x=-13 | | 5.5x+1.2-0.3=7.2x-3 | | 13=4x?9 | | 12+x^2=8y-y^2 | | -2[3+4(x-1)]=x | | x+2x+3x=306 | | -3-66x=9 | | 5.2x=3x | | 1=2(12) | | 196-36x^2=0 | | 6x=306 | | -16x+3=37+x | | 6q+1=31 | | pq+3p= | | 3y-4=3--2y |